Evidence of dispersal between the Yenisei and the Lena river basins during the late Pleistocene within the whitefish (Coregonus lavaretus pidschian) complex - Bochkarev, Nickolay A.; Zuykova, Elena I.; Katokhin, Alexey V.; Andree, Karl B.; Solovyev, Mikhail M. (Canadian Journal of Zoology, 2021)
The Coregonus lavaretus (Linnaeus, 1758) complex is a morphologically and genetically diverse group of whitefish. Its taxonomic structure has been controversial for almost a century. At least 25 forms of C. lavaretus have been described in Siberia, but there is still no consensus on their intraspecific structure and taxonomy. Coregonus lavaretus pidschian (Gmelin, 1789) was described as a subspecies of C. lavaretus. Recently, it was assumed that this subspecies is also a complex. The purpose of this study was to compare the distributions of pidschian-like whitefish haplotypes in two basins of large Siberian rivers, Yenisei and Lena, and to assess the gene flow between basins of these rivers, which were connected after the last glaciation. The sequence of the following mitochondrial DNA genes, 16S rRNA (partial), tRNA-Leu (full), NADH dehydrogenase subunit 1 (full), tRNA-Ile (full), and tRNA-Gln (partial), were used for the inference of intraspecific genetic structure of C. l. pidschian. Whitefish haplotypes were clustered into two groups according to their distribution between two large Siberian river basins; however, there were shared haplotypes indicating events of migration and hybridization, which could occur when Bolshoi Yenisei and Lena river systems were connected after the last glaciation (the Late Pleistocene).